Entre os muros da escola: posicionamentos de estudantes sobre sexualidade e gênero - Meneses, Roberta Caldas Domingues de (2015)
The present study is aimed to problematize teenager's stand in regard to gender and sexuality emerged from the context of a private school located at the city of João Pessoa. Many aspects were analyzed such as school context and its mechanisms of adolescent's body discipline; the meanings given to the body by these teenagers and their relations with Regimes of truth; the meanings and significance given to sexuality and it's perceptions of gender differences in relation with sexual practices. Research was a qualitative one and it used the ethnographic method where the researcher is supposed to be inserted in the environment investigated. According to the ethnographic method, the instrument utilized was the Field Diary, associated with the Focus Group, technique which favors debate, exchange of experiences, and allows interventions among participants; and, a social-demographic list of questions. Were considered as participants on this network of enunciation, all of those observed, since all of them produced data. In this perspective, even the researcher was considered a source of data, along with the students who composed the Focal Groups, teachers and all school staff observed. The students participants composed two Focal Groups. The first was composed by seven students, one male and six females, all aged between fourteen and fifteen. The second group was composed by nine female students aged between fifteen and sixteen. The analysis of the data produced looked for analyzing speech from a foulcauldian perspective. Results have shown that discipline mechanisms utilized in school context, primarily based on constant vigilance and behavior control of the students, lead to their classification and standardization. The speeches pointed to a necessity of adaptation of the figure to beauty standards featured in a healthy body. Sexuality was associated to speeches about sexual initiation, precautions and adolescent pregnancy. It was also observed that understanding of differences among gender is marked by female subjection as a given state, that is, naturalized. We conclude that the adolescent's speech expressed the predominance of a morally accepted stand, filled, however, with rupture and contradiction.